SOEP-Core - 2019: Design, nonresponse, and weighting in the Sample Q (queer) - Lisa de Vries; Mirjam Fischer; Martin Kroh; Simon Kühne; David Richter (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This report details the design of the boost Sample Q to the SocioEconomic Panel (SOEP) in 2019. Sample Q supplemented the SOEP Core sample by queer households, including gender and sexual minorities such as lesbian, gay, bisexual, and trans* respondents (LGBTQ*). Recruitment of these households was performed by a random telephone screening of adults living in Germany. Sample Q comprises of 477 newly recruited LGBTQ*queer households and this boost sample thus augments the 405 already existing queer households in the SOEP to a total of 882 households with 1,237 respondents identifying as sexual and gender minority.
Keywords: 330